Comparative analysis of different identification techniques for detection of mycobacterial species in clinical samples - Umrao, Jyoti; Sivaperumal, R (Journal of Drug Delivery and Therapeutics, 2018)
Out of 906 cultures isolates, 263 (29.0%) were confirmed as NTM and 724 (71.0%) were identified as Mycobacterium tuberculosis complex. The diversity of NTM species was high and predominated by Mycobacterium abscessus (31.3%) followed by M. fortuitum (22%), M. intracellulare (13.6%), M. chelonae (9.1%), however, M. abscessus and M. fortuitum were the predominant species in both types of clinical isolates. Men (60.4%) and older patients aged greater than 55 years were the predominated risk group for NTM infection. Additionally, three HIV/AIDS cases (1.1%), as well as thirty five cases were found to be type two diabetes mellitus infected with non-tuberculous bacteria. Keywords: NTM, Technique, BacT/Alert, Biochemical Test, Tuberculosis.